Characterization of BET, XRF and weight loss on dolomite and calcined dolomite heated at different heating time - Mokhzani Khair, Ishak; Khairul Nizar, Ismail; Banjuraizah, Johar; Kamarudin, Hussin; Wan Mohd Sabki, Wan Omar (Universiti Sains Malaysia (USM), 2011)
4th International Conference on Recent Advances in Materials, Minerals and Environment and 2nd Asian Symposium on Minerals and Processing (RAMM & ASMP 2009) organized by Universiti Sains Malaysia (USM), Japan Society of Mechanical Engineers, Institute of Materials Malaysia (Northen Region), Advanced Materials Processing and Intergrity Group UKM, Malaysian Chambers of Mine and Institute of Minerals Engineer, 1st - 3rd June 2009 at Bayview Beach Resort, Penang.